Growth and reproductive performance of the indigenous Kedah-Kelantan (KK) cattle: a review - Islam, Mohammed Sirajul; Degu, Nurhusien Yimer; Haron, Abd Wahid; Abdullah, Faez Firdaus Jesse; Hiew, Mark Wen Han; Wan Jaafar, Wan Nor Fitri (Universiti Putra Malaysia Press, 2021)
Kedah-Kelantan (KK) cattle plays a significant role for beef industry in Malaysia. KK cattle is a well-adapted local breed reared by traditional farming system with low quality feeds. KK cows normally produce a calf per year, which attracts farmers for commercial production. Currently, KK cattle is playing an important role for profitable beef production in Malaysia since the imported exotic breeds, crossbreds, and synthetic breeds of cattle could not perform to their full potential for sustainability of the livestock industry in the country. Consequently, nowadays, importance of the unique Malaysian beef breed (KK) has been increasing gradually in consideration to the changing climatic situation and adaptibility. Meanwhile, it is required to know the productive and reproductive performance of KK cattle for a further long term sustainable breeding program. As such reviewing growth performance, age at puberty and maturity, semen quality, scrotal biometry, libido efficiency, conception rate, service per conception, and calving interval are fundamental. There exist limited systemic studies and in-depth reviews based on these key reproductive, growth characteristics, and indexes for KK cattle. Therefore, reproductive key parameters of KK cattle were reviewed with the aim of understanding the challenges on the production of KK cattle and to suggest possible strategies to alleviate those challenges.